A cobrança de ISS de empresas de intermediação de contratos privados de transporte de passageiros que atuem no país por meio de aplicativos digitais - Nascimento, Hérica Cristina Paes (Universidade do Vale do Rio dos Sinos, 2023)
The present work had as its main research objective to verify the possibility of making feasible the constitutional and legal framework for the collection of the Tax on Services (ISS) within the municipality of embarkation and disembarkation of passengers who use the private transport services of structured companies and active in digital platforms and that carry out the intermediation of private contracts of these passengers through internet application providers. We also sought to bring elements that demonstrate how digital transformation can affect the taxation of companies inserted in the so-called digital economy. Initially, this dissertation brings in its introduction a broader and clearer exposition of the research problem, with its secondary objectives and is followed by an explanation of the research method used, called Design Science Research, which seeks to build artifacts and structures capable of bring benefits to society. The third chapter is dedicated to starting the theme itself, bringing the result of research related to the transformation that emerging technologies have provided for companies, affecting traditional taxation that cannot effectively keep up with the advancement of the digital economy. The fourth chapter specifies the research that is the main object of this dissertation and demonstrates the need for a new tax interpretation that considers the absence of physical establishment of technology companies for their effective functioning, in comparison with traditionally constituted companies, at the same time that, due to technology, they are present in all states of the country and in countless municipalities, given their ubiquitous nature. We tried to demonstrate that the collection of the Tax on Services is in line with the Brazilian legal system, so that, for the effective collection of the tax by the Brazilian municipalities, a legislative modification without many obstacles will be necessary, following the work to its conclusion with the final proposition of a more current bill that, if approved, could promote a better tax distribution among Brazilian municipalities, which will contribute to its practical applicability in an effective, concrete way and more adherent to the constitutional tax principles. In addition to the specific methodology used to guide the completion of this work, bibliographical research and the documental research method were also used.
Keywords: Tributação; Economia digital; Imposto sobre serviços; Taxation; Digital economy; Tax over services; ACCNPQ::Ciências Sociais Aplicadas::Direito